Analis Kemampuan Guru Kelas dalam Menyusun RPP melalui Supervisi Klinis di SDN Wukirsari 02 - Romyati Romyati; Nur Fajrie; Sri Surachmi W (Journal on Education, 2023)
This study aims to describe the ability of teachers to prepare lesson plans, as well as to increase the professionalism of teachers in carrying out their main tasks and functions as teaching staff in order to increase teacher insight, knowledge and skills regarding teacher competence and improve teacher quality in managing classroom administration through clinical supervision. The author used a qualitative narrative research method, a type of classroom action research. The subjects in this study were 6 teachers at SDN Wukirsari 02. Data collection techniques using observation, interviews, and documentation. The results of this study indicate that the teacher's ability to prepare lesson plans can be increased by holding clinical supervision. In addition to increasing students' learning achievement, it is also followed by changes in teacher attitudes both from the planning aspect (RPP) and the implementation of learning